Interferensi Sintaksis Bahasa Mandailing Pada Mahasiswa Prodi Tadris Bahasa Indonesia - Devi Hertina, Rina Devianty, Nisa Hafziyah, Aulia Meylani, (EUNOIA (Jurnal Pendidikan Bahasa Indonesia), 2023)
Interference is defined as a mixture in the field of language. Interference in language can affect all aspects of grammar such as syntax. This study aims to discuss the syntactic interference of the Mandailing language for students of the Indonesian Tadris Study Program. At the same time to describe (1). the influence of interference between the Mandailing language and Indonesian on the Indonesian language study program; (2). factors that cause language interference; (3). comparison of the interference of the Mandailing and Indonesian languages in the form of interference of words, phrases and clauses in sentences. This research uses a qualitative approach, while the type of research is descriptive research. The location of this research is in the State Islamic University of North Sumatra. Of course it involves Indonesian Tadris students. The research data is in the form of a regional language (mandailing) which is commonly used by students in Indonesian language schools and its surroundings. The data source is determined by snowball sampling technique. The research data was collected by observation techniques, interviews. The results of this study are the interference of the Mandailing language syntax in students of the Indonesian Tadris Study Program.